Usos Dialectales y Usos No Hispánicos: La Postura Académica y Su Repercusión en Los Medios de Comunicación - Pedrero González, Amalia (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
The aim of this paper is to reinforce - the correct use of Spanish in the Mass Media. An example shows the differences in the normative uses of dialectalisms and non-Hispanic terms. The Academic position on these types of terms will be stated, based in academic evidences as well as in quantitative surveys on both kinds of words. The adequate use of them will be explained in this work, too.
Keywords: Spanish in the Mass Media; Dialectalism; Non Hispanic terms